Genetic basis of host - specificity in Sclerospora graminicola, the pearl millet downy mildew pathogen - V.S. GUPTA1, and P.K. RANJEKAR1, J.G. SASTRY1, S. SIVARAMAKRISHNAN2, V.P. RA02, R.P. THAKUR2, R.S. SINGRU1, (Indian Phytopathology, 2002)
The genetic basis of host specificity in Sc/erospora graminicola, the causal agent of downy mildew in pearl millet, was studied in a host-pathogen cross-inoculation experiment. Two pathotypes, Path-I and Path-5 selected from hybrid NHB 3 (genetically uniform) and landrace population 700651 (genetically heterogeneous), respectively, was cross inoculated under controlled conditions in a glasshouse. The pathotypes were maintained for 10 asexual generations by serial passage on the seedlings of their respective hosts. Pathogenicity test with Path-I indicated an increase in virulence over its new host, 700651, compared with the adapted host, NHB 3. However, it was not true for Path-5 with NHB3. Of 120 RAPD primers tested for polymorphism between generations of the isolates, only two primers (1-1 and 1-10) could detect variations in Path-I and only one primer (J-18) in Path-5. The DNA fingerprinting profile of the isolates obtained after 10 generations revealed differences within the microsatellite probe (GATA). compared with the initial generation. The change in virulence in Path-I and its' adaptation to the new host, 700651, was demonstrated by the change in RAPDs and DNA fingerprinting profile in the two extreme generations. Implications of these results in understanding the genetic basis of emergence of new pathotypes were also discussed.